2018
DOI: 10.4103/ejd.ejd_249_17
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of computer-guided surgery for dental implant placement in fully edentulous patients: A systematic review

Abstract: Assess clinical studies regarding accuracy between virtual planning of computer-guided surgery and actual outcomes of dental implant placements in total edentulous alveolar ridges. A PubMed search was performed to identify only clinical studies published between 2011 and 2016, searching the following combinations of keywords: “Accuracy AND Computer-Assisted Surgery AND Dental Implants.” Study designs were identified using the terms: Case Reports, Clinical study, Randomized Controlled Trial, Systematic Reviews,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
55
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(63 citation statements)
references
References 20 publications
0
55
1
2
Order By: Relevance
“…Skjerven et al [22] also concluded that the main deviation was angular in their clinical study. Many variables that could affect the accuracy of sGIS have been proposed and investigated, including the location of implant site [29][30][31], jaw position [5,18,32,33], alveolar bone quality [16,30], implant length [31,34], implant diameter [35], guide support [34,36], and the flap or flapless approach [1,4,20,36,37]. In the present study, however, none of the above-mentioned variables were found to have significant influence on the accuracy of sGIS.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Skjerven et al [22] also concluded that the main deviation was angular in their clinical study. Many variables that could affect the accuracy of sGIS have been proposed and investigated, including the location of implant site [29][30][31], jaw position [5,18,32,33], alveolar bone quality [16,30], implant length [31,34], implant diameter [35], guide support [34,36], and the flap or flapless approach [1,4,20,36,37]. In the present study, however, none of the above-mentioned variables were found to have significant influence on the accuracy of sGIS.…”
Section: Discussioncontrasting
confidence: 62%
“…In the literature, the accuracy of sGIS using conventional planning workflow had been extensively examined. [2,[16][17][18][19][20][21]. One in vivo study investigating the accuracy of the sGIS by a fully digital planning modality has been reported [22].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, systematic reviews suggest that tooth-supported templates yield the highest accuracy (Marliere, Demetrio, Picinini, Oliveira, & Chaves Netto, 2018;Tahmaseb et al, 2014;Van Assche et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In total edentulous jaws it was recommended that the guide covers most of the space and fixed with two anterior and two posterior pins. 18,19 The development of a locator for the drills within the bone can be of great benefit, both with and without the detachment of the flap surgery.…”
Section: Discussionmentioning
confidence: 99%